2020
DOI: 10.1002/advs.202000467
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Efficacy of Metal‐Free MRI Contrast Agents via Conjugating Nitroxides onto PEGylated Cross‐Linked Poly(Carboxylate Ester)

Abstract: Herein, two water‐soluble PROXYL‐based magnetic resonance imaging (MRI) macromolecular organic contrast agents (mORCAs) are designed and synthesized: linear and cross‐linked PCE‐mPEG‐Ppa‐PROXYL. They are prepared by conjugating linear and cross‐linked poly(carboxylate ester) (PCE) with poly(ethylene glycol) (mPEG 2000 )‐modified nitroxides (PROXYL), respectively. Both mORCAs form self‐assembled aggregates in an aqueous phase and PROXYL is protected inside a hydrophobic core to achieve gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 51 publications
0
40
0
1
Order By: Relevance
“…Implanted hydrogels should ideally have tunable biodegradation kinetics profiles to either match the rate of neo‐tissue regeneration, [ 59 ] or to degrade in a controlled manner after completion of their initial objective (i.e., imaging, drug delivery). [ 60,61 ] To evaluate the biodegradation properties of Si‐HA hydrogels, various gel formulations (DS = 13.5–57.7%) were injected in the subcutis of immunocompetent mice under aseptic conditions, and submitted to two volume assessment methods after 7 and 21 d. This model is particularly useful to obtain general information on degradation rates and inflammatory response following hydrogel injection, in anticipation of future applications in vascularized tissues. [ 62 ] As a first semiquantitative approach, a daily palpation test was performed to assess the in vivo erosion of hydrogels over time ( Figure A,C).…”
Section: Resultsmentioning
confidence: 99%
“…Implanted hydrogels should ideally have tunable biodegradation kinetics profiles to either match the rate of neo‐tissue regeneration, [ 59 ] or to degrade in a controlled manner after completion of their initial objective (i.e., imaging, drug delivery). [ 60,61 ] To evaluate the biodegradation properties of Si‐HA hydrogels, various gel formulations (DS = 13.5–57.7%) were injected in the subcutis of immunocompetent mice under aseptic conditions, and submitted to two volume assessment methods after 7 and 21 d. This model is particularly useful to obtain general information on degradation rates and inflammatory response following hydrogel injection, in anticipation of future applications in vascularized tissues. [ 62 ] As a first semiquantitative approach, a daily palpation test was performed to assess the in vivo erosion of hydrogels over time ( Figure A,C).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years several studies have shown the ability of stimuli-responsive copolymer-drug bioconjugates to significantly improve the therapeutic index of the active compounds by means of increased accumulation in the tumor sites ( Chen et al, 2019b ; Zheng et al, 2019 ; Cai et al, 2020 ; Guo et al, 2020 ; Pan et al, 2020 ; Zhang et al, 2020 ). For example, Chen and coworkers developed two strategies to achieve this goal: a) through use of N-(1,3-dihydroxypropan-2-yl) methacrylamide with a high molecular weight (MW) linked to doxorubicin by an enzyme-responsive oligopeptide linker and b) by modifying the previously-decribed polymeric derivative by grafting PEG via a disulfide bond.…”
Section: Drug Targetingmentioning
confidence: 99%
“…Introduction of the MR contrast agent into to the tissue of interest offers accurate and detailed information about cancer infiltration, cancer progression, and tumoral vascular distribution (Cao et al, 2020; H. Liu, Chu, et al, 2018). However, clinically used Gd‐based MR contrast agents have a short imaging duration time, non‐tumor specificity, and a low longitudinal relaxation efficacy, therefore, they have a poor performance in cancer diagnosis (S. Guo, Wang, et al, 2020).…”
Section: Applications Of Dendritic Nano‐scale Systems In Cancer Diagnmentioning
confidence: 99%